Biliary drainage in malignant biliary obstruction: an umbrella review of randomized controlled trials - Wang, Yaoqun; Wen, Ningyuan; Xiong, Xianze; Li, Bei; Lu, Jiong (Frontiers in Oncology, 2023)
Background There are still many controversies about biliary drainage in MBO, and we aimed to summarize and evaluate the  evidence associated with biliary drainage. Methods We conducted an umbrella review of SRoMAs based on RCTs. Through July 28, 2022, Embase, PubMed, WOS, and Cochrane Database were searched. Two reviewers independently screened the studies, extracted the data, and appraised the methodological quality of the included studies. GRADE was used to evaluate the quality of the evidence. Results: 36 SRoMAs were identified. After excluding 24 overlapping studies, 12 SRoMAs, including 76 RCTs, and 124 clinical outcomes for biliary drainage in MBO were included. Of the 124 pieces of evidence evaluated, 13 were rated “High” quality, 38 were rated “Moderate”, and the rest were rated “Low” or “Very low”. For patients with MBO, 125I seeds+stent can reduce the risk of stent occlusion, RFA+stent can improve the prognosis; compared with PC, SEMS can increase the risk of tumor ingrowth and reduce the occurrence of sludge formation, and the incidence of tumor ingrowth in C-SEMS/PC-SEMS was significantly lower than that in U-SEMS. There was no difference in the success rate of drainage between EUS-BD and ERCP-BD, but the use of EUS-BD can reduce the incidence of stent dysfunction. For patients with obstructive jaundice, PBD does not affect postoperative mortality compared to direct surgery. The use of MS in patients with periampullary cancer during PBD can reduce the risk of re-intervention and stent occlusion compared to PC. In addition, we included four RCTs that showed that when performing EUS-BD on MBO, hepaticogastrostomy has higher technical success rates than choledochoduodenostomy. Patients who received Bilateral-ENBD had a lower additional drainage rate than those who received Unilateral-ENBD. Conclusions Our study summarizes a large amount of evidence related to biliary drainage, which helps to reduce the uncertainty in the selection of biliary drainage strategies for MBO patients under different circumstances.